2013
DOI: 10.1038/nature12496
|View full text |Cite
|
Sign up to set email alerts
|

Microbial colonization influences early B-lineage development in the gut lamina propria

Abstract: The RAG1/RAG2 endonuclease ("RAG") initiates the V(D)J recombination reaction that assembles Ig heavy (IgH) and light (IgL) chain variable region exons from germline gene segments to generate primary antibody repertoires1. IgH V(D)J assembly occurs in progenitor (pro-) B cells followed by that of IgL in precursor (pre-) B cells. Expression of IgH μ and IgL (Igκ or Igλ) chains generates IgM, which is expressed on immature B cells as the B cell antigen-binding receptor ("BCR"). Rag expression can continue in imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
180
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(199 citation statements)
references
References 32 publications
10
180
0
1
Order By: Relevance
“…B1a cells are predominantly formed during the perinatal period (42). At this stage, the gastrointestinal tract is colonized by commensal bacteria from food, resulting in an enormous boost of the mucosal immune system and shaping of the B cell compartment (43). To prevent opportunistic infection of the peritoneum, the innate B cell response must therefore limit bacterial expansion at this site (15).…”
Section: Discussionmentioning
confidence: 99%
“…B1a cells are predominantly formed during the perinatal period (42). At this stage, the gastrointestinal tract is colonized by commensal bacteria from food, resulting in an enormous boost of the mucosal immune system and shaping of the B cell compartment (43). To prevent opportunistic infection of the peritoneum, the innate B cell response must therefore limit bacterial expansion at this site (15).…”
Section: Discussionmentioning
confidence: 99%
“…The net effect is the induction of B-cell tolerance to such resident microorganisms, and the increase of the repertoire of B-cell receptors [64].…”
Section: Systemic Chronic Inflammation Microbiota and Ncdsmentioning
confidence: 99%
“…Another study showed that short-chain fatty acids also regulate T reg and prevent T cell transfer colitis, possibly through similar mechanisms [35]. B cells are also affected by microbes as early development and recombination of immunoglobulin receptors on early B-lineage takes place in the gut lamina propria [36]. Although not directly related to gut immunity, microbes have also been shown to activate sensory neurons in the skin, leading directly to pain and inflammation [37].…”
Section: Translating Bugs Into Care: What the Future Might Look Likementioning
confidence: 99%